Evaluating health literacy of Kerman Medical University, School of Public Health students about recycling solid waste - Hashemi, Majid (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: The increasing trend in waste production and its improper disposal in the environment have led to mismanagement of national resources and hazards to the natural environment. Therefore, the recycling of solid waste can help prevent economic and bio-environmental disasters. The aim of this study was to evaluate the health literacy of the students of the Kerman Public Health School about the management and recycling of solid waste. MATERIALS AND METHODS: This was a cross-sectional study and the target population was all of the students of the Kerman Public Health School (421 students) in five fields. A questionnaire including demographic and health literacy questions was distributed among the students. RESULTS: The male students answered the questions significantly more than female students (P<0.001). The Environmental Health students acquired a higher score than all other students and health literacy significantly increased as the student's studying degree promoted (P<0.001). Also, as the number of trimesters increased, health literacy significantly increased (P<0.001). The parents’ education, the family income, and number of people in the family had no significant effect on health literacy. All students believed recycling is important and more than 50% had acquired their knowledge from their academics. CONCLUSION: This survey showed that although students in health-related fields confirm the necessity of recycling solid waste, they still need more education in health literacy as they are supposed to be the promoters of public health in the society in the near future.